EXAMINING THE RELATIONSHIP BETWEEN HEALTH ADMINISTRATION LEADERSHIP STYLES AND EMPLOYEE JOB SATISFACTION IN HAFAR ALBATIN HEALTH FACILITIES - Majed Abdullah Alanazi, Humaidi Ali Alanazi, Ahmed Helail Aldhafeeri, Qaisum Awdah Alenazi, Fahad Dakel Alharbi, Faleh Awad Alharbi, Ray Abdullah Inad Alanazi, Bder Mutlaq Alshammari, (Chelonian Research Foundation, 2022)
Leadership styles in health administration play a crucial role in shaping employee job satisfaction and organizational performance. This study aims to examine the relationship between health administration leadership styles and employee job satisfaction in Hafar AlBatin health facilities, Saudi Arabia. A mixed-methods approach was employed, involving a survey of 200 healthcare employees and semi-structured interviews with 20 health administration leaders. The survey assessed perceptions of leadership styles (transformational, transactional, and laissez-faire) and job satisfaction using the Multifactor Leadership Questionnaire (MLQ) and the Job Satisfaction Survey (JSS). The interviews explored leaders' perspectives on their leadership styles and strategies for promoting employee job satisfaction. The findings revealed a significant positive relationship between transformational leadership and job satisfaction, while laissez-faire leadership was negatively associated with job satisfaction. Transactional leadership showed a weak positive relationship with job satisfaction. The study highlights the importance of adopting transformational leadership practices in health administration to enhance employee job satisfaction and organizational performance. Keywords: health administration, leadership styles, job satisfaction, transformational leadership, Saudi Arabia